Predictors of pain behaviors in fibromyalgia syndrome - Thieme, Kati; Spies, Claudia D.; Sinha, Pranav; Turk, Dennis C.; Flor, Herta (Arthritis care & research, 2005)
Objective To evaluate the contributions of physical, pain-related, cognitive, stress-related, affective, and spouse-related variables to differences in pain behaviors in subgroups of patients with fibromyalgia syndrome (FMS). Methods One hundred forty FMS patients underwent medical, physical, and psychological evaluation. Patients and 30 pain-free controls performed a routine physical activity (window-washing task) to elicit pain behaviors with or without the presence of their spouses. The behaviors and spouses' responses during this task were videotaped and subsequently rated. Patients were classified as dysfunctional (DYS), interpersonally distressed (ID), or adaptive copers (AC) based on responses to the Multidimensional Pain Inventory. Hierarchical regression analyses were used to identify predictors of pain behaviors for the total group and subgroups of patients. Results Patients classified as DYS demonstrated the highest number of pain behaviors compared with those classified as ID or AC. This difference was observable when the spouse was present. Spouse responses and physical variables were significantly related to pain behaviors in the DYS and ID groups with the model accounting for 77.1% and 41.9% of the variance, respectively. In contrast, for the AC group, stress factors were the most significant predictor of pain behaviors, accounting for 22.8% of the variance. Conclusion The results indicate that different variables account for the presence of pain behaviors in different subgroups of patients. The data provide support for the heterogeneity of the diagnosis of FMS and have implications for treatment of subgroups of patients.
Gesehen am 04.11.2020